Framework to Development of Disaster Mitigation Model in Mountain Tourism Destination - Ismail, Jalu Rafli; Kastolani, Wanjat (Department of Urban and Regional Planning, Diponegoro University, 2024)
The geographic position of Indonesia provides both disaster threat and natural resources potential. Indonesia is an archipelagic country located between three major tectonic plates, namely Indo-Australia; Pacific; and Eurasia. Consequently, numerous of active volcanoes and faults are spread across the islands. Indonesia’s unique landforms are often utilized as a unique tourism spot. Along the mountain ranges of Bogor and Cianjur, Bandung, and Garut to Tasikmalaya, various volcanic tourism spots exist side-by-side with the threat of volcanic eruption, mass movements, and earthquake. Therefore, disaster mitigation had to be properly planned to guarantee the sustainability of businesses and investments, as well as for tourists’ safety. This research aims to develop the mitigation model for mountain tourism destinations in West Java Province. Three of currently developing mountain tourism spots are Gede-Pangrango Mountain, Tangkuban Parahu Mountain, and Guntur Mountain. Design of this research is R&D through the 4-D model, consists of Define, Design, Develop, and Disseminate. Disaster mitigation model planning involves research subjects consisting of tourism destination management and local communities. Research instruments used include interviews and observations. The data obtained consists of information regarding disaster perceptions and severity measurements through observations. The developed mitigation model is subsequently validated by experts and research subjects to assess its suitability. The output of the development is a “Conceptual Model”, which is a participative mitigation strategy between tourism destination management and local communities. This conceptual mitigation model can be utilized by policymakers as a foundation for monitoring the spread of tourist destinations in facing natural disaster threats.